Burden of Norovirus in the United States, as Estimated Based on Administrative Data: Updates for Medically Attended Illness and Mortality, 2001–2015. (14th April 2020) - Burke, Rachel M; Mattison, Claire P; Pindyck, Talia; Dahl, Rebecca M; Rudd, Jessica; Bi, Daoling; Curns, Aaron T; Parashar, Umesh; Hall, Aron J
Abstract: Background: Up-to-date estimates of the burden of norovirus, a leading cause of acute gastroenteritis (AGE) in the United States, are needed to assess the potential value of norovirus vaccines in development. We aimed to estimate the rates, annual counts, and healthcare charges of norovirus-associated ambulatory clinic encounters, emergency department (ED) visits, hospitalizations, and deaths in the United States. Methods: We analyzed administrative data on AGE outcomes from 1 July 2001 through 30 June 2015. Data were sourced from IBM MarketScan Commercial and Medicare Supplemental Databases (ambulatory clinic and ED visits), the Healthcare Utilization Project National Inpatient Sample (hospitalizations), and the National Center for Health Statistics multiple-cause-of-mortality data (deaths). Outcome data (ambulatory clinic and ED visits, hospitalizations, or deaths) were summarized by month, age group, and setting. Healthcare charges were estimated based on insurance claims. Monthly counts of cause-unspecified gastroenteritis-associated outcomes were modeled as functions of cause-specified outcomes, and model residuals were analyzed to estimate norovirus-associated outcomes. Healthcare charges were estimated by applying average charges per cause-unspecified gastroenteritis encounter to the estimated number of norovirus encounters. Results: We estimate 900 deaths (95% confidence interval [CI], 650–1100), 109 000 hospitalizations (95% CI, 80 000–145 000), 465 000 ED visits (95% CI, 348 000–610 000), and 2.3 million ambulatory clinic encounters (95% CI, 1.7–2.9 million) annually due to norovirus, with an associated 430–740 million in healthcare charges. Conclusions: Norovirus causes a substantial health burden in the United States each year, and an effective vaccine could have important public health impact. Abstract : Using administrative data, norovirus was estimated to cause approximately 900 deaths, 109 000 hospitalizations, 465 000 emergency department visits, and 2.3 million ambulatory clinic encounters annually. Rates of outpatient encounters were highest among children, whereas hospitalization and death rates were highest among the elderly.